"This Is Our House!" Why Are I-O Psychologists Losing at the Gender Disparity Game?. Issue 4 (22nd November 2017) - Huffman, Ann Hergatt; Howes, Satoris S.; Olson, Kristine J.
Abstract : Aguinis et al. (2017 ) highlighted the gender disparity in authorship of publications within the field of industrial and organizational (I-O) psychology. We agree with the authors that this is a troubling finding and think that this gender disparity within our field is the most critical implication of the focal article. I-O psychologists are specifically trained to address employment issues, including gender disparities at work. To see such disconcerting findings in our area of expertise is akin to a sports team losing to a competitor when they have the home court advantage. Namely, we are left feeling deflated and asking ourselves, "What went wrong?"